2019
DOI: 10.1177/0391398819837686
|View full text |Cite
|
Sign up to set email alerts
|

Severe quetiapine voluntary overdose successfully treated with a new hemoperfusion sorbent

Abstract: Quetiapine overdose, although rare, is mainly linked with tachycardia, QTc-interval prolongation, somnolence, coma, hyperglycemia, and eventually hepatotoxicity and myocarditis. Extracorporeal techniques for quetiapine removal might be helpful, but only a few cases are reported in the literature. We here describe the case of a 27-year-old healthy woman, admitted to our Intensive Care Unit after voluntary quetiapine intake and successfully treated with CytoSorb hemoperfusion in combination with continuous renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Several case reports have documented the potential benefit of CytoSorb hemoadsorption in severe intoxications (e.g., flecainide [4], quetiapine [5], and venlafaxine [6]). However, the present study is the first to report on the successful use of CytoSorb for severe digitoxin intoxication.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Several case reports have documented the potential benefit of CytoSorb hemoadsorption in severe intoxications (e.g., flecainide [4], quetiapine [5], and venlafaxine [6]). However, the present study is the first to report on the successful use of CytoSorb for severe digitoxin intoxication.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…On the other hand, this might represent an opportunity for therapeutic use in detoxification. A recent case report demonstrated that use of the CytoSorb hempoadsorption was associated with an accelerated reduction in quetiapine plasma levels 7 . However, concentrations of its active metabolite norquetiapine as well as pre‐ and post‐cartridge quetiapine measurements to directly assess adsorber effectiveness had not been performed.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Maximization of blood flow rapidly leads to high clearance in time-critical situations. The duration of therapy, blood flow rates, and changing intervals considering the adsorber saturation kinetics should be individually adjusted to achieve optimal clearance [ 127 , 141 , 142 , 143 , 144 ].…”
Section: Hemoadsorption With Cytosorb ®mentioning
confidence: 99%